Changing anatomies of Information Literacy at the postgraduate level: refinements of models and shifts in assessment - Špiranec, Sonja; Banek Zorica, Mihaela (2012)
In this paper fundamental principles that might inform a theoretical approach to Information Literacy (IL) on the postgraduate level will be identified. Those are based on following premises: 1. the aims of postgraduate/doctoral studies are different in comparison to earlier educational levels and face specific challenges due to the heterogeneity of student population 2. IL frameworks have to acknowledge and address this challenge by adjusting to specific needs of postgraduate students who operate in new information environments 3. new modes of assessment are needed as a result of profound changes in information environments and patterns of generation and use of scientific information Teaching students in the scientific method and culture has long been recognized as the major focus of postgraduate education. An important precondition for efficient research practices is the adequate performance in finding, managing and generating information. Therefore, information literacy as the ability of finding, using and evaluating information can be perceived as central to learning and research. IL on postgraduate levels has a strong focus on the universe of scientific information, which itself went through tremendous changes in the last decade, particularly as a result of the appearance of the Web 2.0 (e.g. Science 2.0, Research 2.0). It has created opportunities for new and alternative forms of research and scholarship that are different from traditional ways of using academic publication or disseminating research results. Such changes suggest renewed conceptions and focal points of IL at the postgraduate level which will take into account new and experimental forms of scholarly communication and the dynamic nature of current information environments. After discussing changes in information landscapes brought about by the Web 2.0 and examining transformed premises of scientific work within such environments, the authors will plea for re-conceptualizations of IL on the postgraduate level and propose new IL principles of assessment that will recognize this transformation.
Projekt MZOS
ENG